2013
DOI: 10.5194/angeo-31-409-2013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a mesospheric bore event over northern China

Abstract: Abstract. A mesospheric bore event was observed using an OH all-sky airglow imager (ASAI) at Xinglong (40.2° N, 117.4° E), in northern China, on the night of 8–9 January 2011. Simultaneous observations by a Doppler meteor radar, a broadband sodium lidar, and TIMED/SABER OH intensity and temperature measurements are used to investigate the characteristics and environment of the bore propagation and the possible relations with the Na density perturbations. The bore propagated from northeast to southwest and divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Simultaneous occurrences of a mesospheric inversion layer (MIL) with a bore event have been reported with optical imaging and lidar observations (She et al, ; Smith et al, ). Simultaneous occurrences of a Doppler duct or a thermal‐Doppler duct have also been reported with optical imaging, radar, and TIMED/SABER (Thermosphere Ionosphere Mesosphere Energetics and Dynamics Satellite/ Sounding of the Atmosphere using Broadband Emission Radiometry) (Bageston, Wrasse, Batista, et al, ; Fechine et al, ; Li et al, , ).…”
Section: Introductionmentioning
confidence: 88%
“…Simultaneous occurrences of a mesospheric inversion layer (MIL) with a bore event have been reported with optical imaging and lidar observations (She et al, ; Smith et al, ). Simultaneous occurrences of a Doppler duct or a thermal‐Doppler duct have also been reported with optical imaging, radar, and TIMED/SABER (Thermosphere Ionosphere Mesosphere Energetics and Dynamics Satellite/ Sounding of the Atmosphere using Broadband Emission Radiometry) (Bageston, Wrasse, Batista, et al, ; Fechine et al, ; Li et al, , ).…”
Section: Introductionmentioning
confidence: 88%
“…The airglow emission intensities were weakened behind the leading bore front in both OH and OI (557.7 nm) images. Li et al () also found a mesospheric bore event propagated into a bright airglow region leaving a dark region behind the leading bore front from an OH all‐sky airglow imager over Xinglong station (40.2 °N, 117.4°E).…”
Section: Observations and Data Analysismentioning
confidence: 93%
“…The bore divides nightglow into bright and dark regions. Since a mesospheric bore was first reported by Taylor et al (), many researchers have devoted much effort to investigating this interesting phenomenon using ground‐based all‐sky airglow imagers (Li et al, ; Medeiros et al, ; Narayanan et al, ; Nielsen et al, ; She et al, ; Shiokawa et al, ; Smith et al, , , , ; Yue et al, ), satellite observation (Miller et al, ), and models (Dewan & Picard, , ; Laughman et al, ; Seyler, ).…”
Section: Introductionmentioning
confidence: 99%
“…Three PMC Turbo images from large‐FOV cameras revealing some of the diversity of dynamics in regions of ~40–60 km in width are shown in Figure . Figure a shows what appears to be a GW front with trailing vortices, an intrusion, or most likely a mesospheric bore at 13:50 UT on 13 July, based on interpretations of similar imaging (Fechine et al, ; Fritts et al, ; Li et al, ; Miller et al, ; Narayanan et al, ; Smith et al, ; and references therein).…”
Section: Pmc Turbo Event Imagingmentioning
confidence: 97%